PERKEMBANGAN POLITIK ISLAM DAN IMPLIKASINYA DALAM PENDIDIKAN ISLAM DI INDONESIA - Handoko Handoko (Ta`Limuna: Jurnal Pendidikan Islam, 2022)
AbstractPolitical developments in Indonesia since the old era (orde lama), the new era (orde baru) until the reform era (pasca-orde baru/reformasi) that occurred in Indonesia is a long history that has implications for various fields of life, including in the field of Islamic education. The political policies that emerged in these various orders certainly greatly influenced the existing policies in Islamic education. This research is library research by reviewing the literature that is in accordance with the topic of the development of Islamic politics in Indonesia and its relation to Islamic education. The results of this discussion include the gap between Islamic education and general education, policies on the legality of Islamic Education in the National Education System, and the portion of Islamic education learning in general education institutions.